2014
DOI: 10.1016/j.nicl.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Independent contribution of individual white matter pathways to language function in pediatric epilepsy patients

Abstract: Background and purposePatients with epilepsy and malformations of cortical development (MCDs) are at high risk for language and other cognitive impairment. Specific impairments, however, are not well correlated with the extent and locale of dysplastic cortex; such findings highlight the relevance of aberrant cortico-cortical interactions, or connectivity, to the clinical phenotype. The goal of this study was to determine the independent contribution of well-described white matter pathways to language function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…More recently, Saporta et al 24 suggested the functional relevance of such a finding after failing to identify the arcuate in 3 patients with congenital perisylvian syndrome and severe language dysfunction. Our results are also in line with work by Paldino et al, 20 who used a machine-learning approach to predict language phenotype on the basis of wholebrain tractography data in a cohort of patients with epilepsy and MCDs. Specifically, they found that the left arcuate fasciculus was an important contributor to the language phenotype.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More recently, Saporta et al 24 suggested the functional relevance of such a finding after failing to identify the arcuate in 3 patients with congenital perisylvian syndrome and severe language dysfunction. Our results are also in line with work by Paldino et al, 20 who used a machine-learning approach to predict language phenotype on the basis of wholebrain tractography data in a cohort of patients with epilepsy and MCDs. Specifically, they found that the left arcuate fasciculus was an important contributor to the language phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…[14][15][16][17][18][19] Recent work has demonstrated the potential for machine learning to translate quantitative data from whole-brain tractography into phenotypic information regarding language function in an individual patient. 20 Although highly accurate, this technique is time-consuming and requires substantial expertise in image processing and mathematics/statistics. These issues constitute a barrier to widespread adoption of such approaches into clinical practice, especially outside academic centers.…”
mentioning
confidence: 99%
“…No model detected a maximum for the uncinate fasciculus, which is reported to develop with reading and language skills (Paldino et al, 2014). These late-developing fiber systems included the superior longitudinal fasciculus, which has been identified in meta-analyses as the tract most consistently reported to be associated with continued development (Peters et al, 2012) and integral to selective functions of verbal fluency, reading (Hoeft et al, 2011; Zhang et al, 2014), vocabulary (Tamnes et al, 2010b), and working memory (Ostby et al, 2011; Vestergaard et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the ability of the model to predict epilepsy duration in each individual was tested in a previously unseen subset of patients. Machine learning approaches, therefore, represent an effective method by which metrics derived from quantitative imaging can be assessed with respect to their potential translation into clinically meaningful information at the level of a single patient (Paldino et al, 2014). Details regarding this particular technique have been previously described (Breiman, 2001).…”
Section: Methodsmentioning
confidence: 99%